Design of microprogrammed controllers with address converter implemented on programmable systems with embedded memories - Wiśniewski, Remigiusz (2011)
In the paper the improvement of a traditional structure of a microprogrammed controller with sharing codes is discussed. The idea is based on the modification of internal modules and connections of the device. Such a solution permits to reduce the number of embedded memories needed for implementation of the microprogrammed controller on programmable structures, especially FPGAs. © 2011 IEEE.